Campylobacter species, Salmonella serotypes and ribosomal RNA-based fecal source tracking in the Kokemäki River watershed - Anna-Maria Hokajärvi; Ananda Tiwari; Pia Räsänen; Laura Wessels; Katri Rankinen; Janne Juntunen; Rudolf J.F. Grootens; Henry Kuronen; Asko Vepsäläinen; Ilkka T. Miettinen; Timo Huttula; Tarja Pitkänen (Science of The Total Environment, 2024)

The contribution of wind wave changes on diminishing ice period in Lake Pyhäjärvi during the last half-century - Tingfeng Wu; Boqiang Qin; Guangwei Zhu; Timo Huttula; Antti Lindfors; Anne-Mari Ventelä; Yongwei Sheng; Richard F. Ambrose (Environmental Science and Pollution Research, 2018)

Presence of active pharmaceutical ingredients in the continuum of surface and ground water used in drinking water production - Heidi Ahkola; Sirkku Tuominen; Sanja Karlsson; Noora Perkola; Timo Huttula; Sami Saraperä; Aki Artimo; Taina Korpiharju; Lauri Äystö; Päivi Fjäder; Timo Assmuth; Kirsi Rosendahl; et al. (Environmental Science and Pollution Research, 2017)

Organic carbon causes interference with nitrate and nitrite measurements by UV/Vis spectrometers: the importance of local calibration - Sari Uusheimo; Tiina Tulonen; Lauri Arvola; Hanna Arola; Jarmo Linjama; Timo Huttula (Environmental Monitoring and Assessment, 2017)

Statistical Dimensioning of Nutrient Loading Reduction: LLR Assessment Tool for Lake Managers - Niina Kotamäki; Anita Pätynen; Antti Taskinen; Timo Huttula; Olli Malve (Environmental Management, 2015)

Simulation tools to support bathing water quality management: Escherichia coli bacteria in a Baltic lagoon - Gerald Schernewski; Elisabeth Fischer; Timo Huttula; Günter Jost; Monique Ras (Journal of Coastal Conservation, 2012)

Air temperature triggers the recovery of evergreen boreal forest photosynthesis in spring - Suni Tanja; Frank Berninger; Timo Vesala; Tiina Markkanen; Pertti Hari; Annikki Mäkelä; Hannu Ilvesniemi; Heikki Hänninen; Eero Nikinmaa; Timo Huttula; Tuomas Laurila; Mika Aurela; et al. (Global Change Biology, 2003)
The timing of the commencement of photosynthesis ( P * ) in spring is an important determinant of growing‐season length and thus of the productivity of boreal forests. Although controlled experiments have shed light on environmental mechanisms triggering release from photoinhibition after winter, quantitative research for trees growing naturally in the field is scarce. In this study, we investigated the environmental cues initiating the spring recovery of boreal coniferous forest ecosystems under field conditions. We used meteorological data and above‐canopy eddy covariance measurements of the net ecosystem CO 2 exchange ( NEE ) from five field stations located in northern and southern Finland, northern and southern Sweden, and central Siberia. The within‐ and intersite variability for P * was large, 30–60 days. Of the different climate variables examined, air temperature emerged as the best predictor for P * in spring. We also found that ‘soil thaw’, defined as the time when near‐surface soil temperature rapidly increases above 0°C, is not a useful criterion for P * . In one case, photosynthesis commenced 1.5 months before soil temperatures increased significantly above 0°C. At most sites, we were able to determine a threshold for air‐temperature‐related variables, the exceeding of which was required for P * . A 5‐day running‐average temperature ( T 5 ) produced the best predictions, but a developmental‐stage model ( S ) utilizing a modified temperature sum concept also worked well. But for both T 5 and S , the threshold values varied from site to site, perhaps reflecting genetic differences among the stands or climate‐induced differences in the physiological state of trees in late winter/early spring. Only at the warmest site, in southern Sweden, could we obtain no threshold values for T 5 or S that could predict P * reliably. This suggests that although air temperature appears to be a good predictor for P * at high latitudes, there may be no unifying ecophysiological relationship applicable across the entire boreal zone.

Development of a deep chlorophyll maximum of Heterocapsa triquetra Ehrenb. at the entrance to the Gulf of Finland - Kaisa Kononen; Maija Huttunen; Seija Hällfors; Patrick Gentien; Michel Lunven; Timo Huttula; Jaan Laanemets; Madis Lilover; Juss Pavelson; Adolf Stips (Limnology and Oceanography, 2003)
The development of a deep chlorophyll maximum (DCM) at a depth of 30–35 m was followed during a 15‐d case study in July 1998 at the entrance to the Gulf of Finland. The study consisted of three 18–24‐h periods of biological (chlorophyll a , phytoplankton, primary production), chemical (nitrate, phosphate) and physical (CTD, turbulence, vertical particle size distribution) measurements at an anchor station and six mesoscale towed CTD/ fluorometer mappings over the surrounding area. Exceptionally cold and windy weather led to a red tide of the dinoflagellate Heterocapsa triquetra instead of the cyanobacterial bloom that frequently occurs in late summer. Comparison of the estimated amount of nitrogen required for an H. triquetra bloom biomass with external loading affirmed that the bloom had been formed on the basis of the nitrate pool below the thermocline. The development of the bloom, therefore, led to the extremely deep nitracline. The DCM formed by H. triquetra developed at the top of the nitracline at an illumination of H. triquetra after an upwelling event that fertilized the upper layer with phosphorus.

Trophic structure of Lake Tanganyika: carbon flows in the pelagic food web - Jouko Sarvala; Kalevi Salonen; Marko Järvinen; Eero Aro; Timo Huttula; Pekka Kotilainen; Heini Kurki; Victor Langenberg; Piero Mannini; Anu Peltonen; Pierre-Denis Plisnier; Ilppo Vuorinen; et al. (Hydrobiologia, 1999)